2005
DOI: 10.1080/13550280590952781
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity regulates viral replication of herpes simplex virus type 1 in the nervous system

Abstract: Herpes simplex virus types 1 and 2 (HSV-1, -2) infect and also establish latency in neurons. In the present study, the authors investigated the influence of neuronal activity on the replication of HSV-1. The results showed that the sodium channel blocker tetrodotoxin (TTX) and the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) could significantly increase viral replication in primary neuronal cultures, by two- to fourfold. In contrast, KCl reduced viral production by at least 80% in the same cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 59 publications
4
17
0
Order By: Relevance
“…Most notably, amino acid metabolic profiling detected significant changes in three non-aromatic amino acids that function as CNS neurotransmitters (aspartate, glutamate, and glycine) and two aromatic amino acids (phenylalanine and tyrosine) that are upstream precursors to two other CNS neurotransmitters, dihydroxyphenylalanine and dopamine [36]. Without regard to the etiopathology of any neurological disease state, this altered amino acid profile is noteworthy in light of previous studies linking other neurotropic viral infections with CNS neurotransmitter dysregulation [37].…”
Section: Discussionmentioning
confidence: 77%
“…Most notably, amino acid metabolic profiling detected significant changes in three non-aromatic amino acids that function as CNS neurotransmitters (aspartate, glutamate, and glycine) and two aromatic amino acids (phenylalanine and tyrosine) that are upstream precursors to two other CNS neurotransmitters, dihydroxyphenylalanine and dopamine [36]. Without regard to the etiopathology of any neurological disease state, this altered amino acid profile is noteworthy in light of previous studies linking other neurotropic viral infections with CNS neurotransmitter dysregulation [37].…”
Section: Discussionmentioning
confidence: 77%
“…Because KCl treatment causes excitotoxicity in neurons and has been previously reported to reduce HSV-1 replication [30], we next pursued an optogenetics approach to modulate neuronal firing activity. Channelrhodopsin 2 (ChR2) is a light-gated ion channel originally isolated from algae, which has become a popular tool to control the activity of neurons using light [31].…”
Section: Resultsmentioning
confidence: 99%
“…Our study was designed to evaluate whether the expression of chosen subunits of GABA A receptors in PBMCs bears any relation to HCV infection and/or the path of HCV RNA elimination after anti-viral treatment. Studies that were carried out on other viruses like herpes simplex virus (HSV) and human immunodeficiency virus (HIV) indicated that the expression of GABA A receptor on the target cells could be modulated upon the viral infection [18, 19]. Although GABA A receptors tend to exist as a pentameric structure consisting of six major GABA A receptor subunits [1], we decided to screen the expression of two of them: α1 and β3.…”
Section: Discussionmentioning
confidence: 99%